Massive accumulation of N‐acylethanolamines after stroke. Cell signalling in acute cerebral ischemia? - Berger, Christian; Schmid, Patricia C.; Schabitz, Wolf‐Ruediger; Wolf, Margit; Schwab, Stefan; Schmid, Harald H. O. (Journal of neurochemistry, 2004)
We investigated levels and compositions of N‐acylethanolamines (NAEs) and their precursors, N‐acyl phosphatidylethanolamines (N‐acyl PEs), in a rat stroke model applying striatal microdialysis for glutamate assay. Rats (n = 18) were treated with either intravenous saline (control), NMDA receptor antagonist MK801 (1 mg/kg), or CB1 receptor antagonist SR141716A (1 mg/kg) 30 min after permanent middle cerebral artery occlusion (MCAO). MK801 significantly attenuated the release of glutamate in the infarcted striatum (79 ± 22 μmol/L) as compared with controls (322 ± 104 μmol/L). The administration of CB1 antagonist SR141716A had no statistically significant effect on glutamate release (340 ± 89 μmol/L), but reduced infarct volume at 5 h after MCAO significantly by approximately 40%, whereas MK801 treatment resulted in a non‐significant (18%) reduction of infarct volume. In controls, striatal and cortical NAE concentrations were about 30‐fold higher in the infarcted than in the non‐infarcted hemisphere, whereas ipsilateral N‐acyl phosphatidylethanolamine (N‐acyl PE) levels exceeded contralateral levels by only a factor of two to three. Treatment with MK801 or SR141716A, or glutamate release in the infarcted tissue, had no significant effect on these levels. NAE accumulation during acute stroke may be due to increased synthesis as well as decreased degradation, possibly by inhibition of fatty acid amide hydrolase (FAAH).